The Association between Free Radicals and the Ovarian Functions: A Review - Sabea Khamees Abed; Husam Hadi Jasim; Mohammed Ali Shahooth; Mustafa A. Saud (مجلة الانبار للعلوم البيطرية)
Metabolites of oxygen are called reactive oxygen species (ROS). They are constantly synthesized by healthy cells are a consequence of aerobic respiration and are necessary for proper cellular function. These species (ROS) cause oxidative stress as a result of generation exceeding the capabilities of the antioxidant system to neutralize it. It is a bifurcating factor in controlling the reproductive system of females, as it can influence various physiological activities or contribute to infertility in females. The current review notes that several ovarian function processes, including reactive oxygen species, have a major impact on follicular formation, ovulation, and corpus luteum function. Scavenging mechanisms also occur. However, the review concentrates on the detrimental impact that elevated ROS production has on the female reproductive system. This review concludes that free radicals play a variety of roles in ovarian function and that excess has negative effects on the female reproductive system.